A new model predictive torque control strategy for permanent magnet synchronous hub motor of EVs. Issue 3 (5th May 2021) - Chen, Long; Xu, Hao; Sun, Xiaodong
This paper presents an optimal control strategy for a permanent magnet synchronous hub motor (PMSHM) of EVs drive using three voltage vectors. First, in order to simultaneously control torque and flux excellently, three voltage vectors including two active vectors and one zero voltage vector are selected. Second, the duration of the three voltage vectors in one period is calculated by the principle of simultaneous deadbeat control of torque and flux. Moreover, the cost function which eliminates the weight coefficient is proposed to reduce the amount of calculation. Finally, the proposed method is compared with the one- and two-vector-based model predictive torque control (MPTC) methods both in simulation and experiment. It is found that the proposed threevector-based MPTC can obtain better performance such as smaller torque ripple and current total harmonic distortion (THD) both in steady and dynamic state.